2019
DOI: 10.1111/clr.13459
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐oral single‐site comparisons of periodontal and peri‐implant microbiota in health and disease

Abstract: Objective: Periodontitis and peri-implantitis are oral infectious-inflammatory diseases that share similarities in their pathology and etiology. Our objective was to characterize the single-site subgingival and submucosal microbiomes of implant-rehabilitated, partially dentate Chinese subjects (n = 18) presenting with both periodontitis and peri-implantitis. Materials and methods:Subgingival/submucosal plaque samples were collected from four clinically distinct sites in each subject: peri-implantitis submucosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
88
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(107 citation statements)
references
References 79 publications
13
88
3
3
Order By: Relevance
“…In the study of Torrungruanag et al (29), the prevalence of P. ginigvalis and T. denticola among patients with severe periodontitis was relatively similar to the detection rate frequency registered in our research, while detection rate frequency of T. forsythia and P. intermedia in our study was comparatively lower, which can be explained by the smaller number of study subjects in the corresponding group. It is important to notice that in both studies the prevalence/ detection frequency of A. actinomycetemcomitans was the lowest both among periodontitis and healthy sites, while bacterial load of this species was also the lowest one.…”
Section: Raspravasupporting
confidence: 85%
See 1 more Smart Citation
“…In the study of Torrungruanag et al (29), the prevalence of P. ginigvalis and T. denticola among patients with severe periodontitis was relatively similar to the detection rate frequency registered in our research, while detection rate frequency of T. forsythia and P. intermedia in our study was comparatively lower, which can be explained by the smaller number of study subjects in the corresponding group. It is important to notice that in both studies the prevalence/ detection frequency of A. actinomycetemcomitans was the lowest both among periodontitis and healthy sites, while bacterial load of this species was also the lowest one.…”
Section: Raspravasupporting
confidence: 85%
“…U istraživanju Torrungruanaga i suradnika (29) prevalencija vrsta P. ginigvalis i T. denticola među pacijentima s teškim parodontitisom bila je razmjerno slična nalazima u našem istraživanju, a učestalost vrsta T. forsythia i P. intermedia u našem istraživanju bila je razmjerno manja, što se može objasniti manjim brojem ispitanika u odgovarajućoj skupini. Važno je istaknuti da je u oba istraživanja prevalencija vrste A. actinomycetemcomitans bila najmanja i u slučaju parodontitisa i u zdravim uvjetima, dok je bakterijsko opterećenje ove vrste bilo najmanje.…”
Section: Raspravaunclassified
“…The oral biofilm consists of a complex bacterial community initiated by free-floating cells adhering to the implant surface. Early colonizers such as S. sanguinis are important in that process, due to their role in the guidance of later colonizers [55,56]. Similarly, species like L. salivarius are important because their by-products are crucial for biofilm formation and maintenance, but also due to their interplay with other species [57].…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature reporting microbial analyses of various percutaneous device interfaces reveals that most studies rely on culture‐based rather than molecular techniques and are not designed as longitudinal analyses and thus do not evaluate changes in the microbiota over time. They are rather “point‐in‐time snapshots” and either imprecisely determine the variety of bacteria comprising the microbiome or fail to do so over time . A single recently published longitudinal study of the skin implant/interface of a bone‐anchored hearing system (BAHS) did use culture‐independent microbial sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that the species compositions of the periodontal and peri‐implant microbiota varied widely between subjects. The inter‐subject variations in subgingival/submucosal microbiome composition outweighed differences observed between implant versus tooth sites, or between diseased versus healthy (unaffected) peri‐implant/periodontal sites . In general, some studies revealed that the genera Streptococcus , Prevotella , and Haemophilus characterized peri‐implant health.…”
Section: Discussionmentioning
confidence: 99%